Analysis of physicochemical properties, electronic sensory, and HS-GC-IMS to explore the effects of density-related stress on the texture, nutritional profile, and flavor of Larimichthys crocea reared in recirculating aquaculture systems - Songpeng Jia; Mengqi Lu; Tianyi Lan; Zhenyu Gao; Ran Meng; Xuelei Wang; Xiongfei Wu; Lin Huang; Xujie Li; Zhongming Zheng; Weiliang Shen (Aquaculture Reports)
ABSTRACT: The large yellow croaker (Larimichthys crocea) is one of the key aquaculture species in China, yet the impact of stocking density on its muscle quality in recirculating aquaculture systems (RAS) remains unclear. This study evaluated the effects of density-related stress on muscle quality through comprehensive physicochemical and sensory analyses, including texture measurement, proximate composition, fatty acid/amino acid profiling, electronic tongue/nose evaluations, and HS-GC-IMS. Juvenile fish (initial weight: 49.26 ± 3.90 g) were cultured for 60 days at low (LSD, 4.01 kg/m³), medium (MSD, 7.01 kg/m³), and high (HSD, 10.01 kg/m³) stocking densities across three RAS units, with a total of 1575 fish. The results indicate that the MSD group showed superior water-holding capacity, higher muscle fiber density, and greater post-heating hardness. All groups had high protein content and essential amino acid profiles meeting FAO/WHO recommendations. The LSD group was enriched in monounsaturated fatty acids and umami-related amino acids, the MSD group had higher crude fat and essential amino acids, while the HSD group showed elevated levels of n-3 polyunsaturated fatty acids such as EPA and DHA. Regarding flavor, the MSD group exhibited higher levels of umami and salty tastes, along with increased concentrations of volatiles associated with fruity and roasted aromas. In contrast, the LSD and HSD groups exhibited higher levels of certain aldehydes and ketones, which may compromise flavor harmony. These findings demonstrate that stocking density significantly influences the muscle quality of L. crocea in RAS.